The biological control of cacti ( cactaceae: opuntioideae) in South Africa: basic of hostselection in the 'stricta' biotype of dactlopius opuntiae (cockerell) (hemiptera: dactylopiidae) - Musengi, Kudakwashe (My University, 2018)
The cochineal insect, Dactylopius opuntiae (Cockerell), plays a major role in the control of Opuntia species. Host preferences of the ‘stricta’ biotype of D. opuntiae are only partially known, as it has not been tested against all Opuntia species; however, it was released 22 years ago in South Africa against Opuntia stricta. The ‘stricta’ biotype of Dactylopius opuntiae can potentially be used against one or more Opuntia species. I investigated the basis of host selection in this cochineal insect. Firstly, I assessed the reproductive performance of the ‘stricta’ biotype of D. opuntiae on Opuntia stricta, Opuntia humifusa and two Opuntia engelmannii lineages. The life-history parameters recorded were crawler development time, crawler survival, female development time, female weight and number of crawlers produced by females. Results revealed large differences in the developmental biology and reproductive performance of the ‘stricta’ biotype of D. opuntiae between the Opuntia hosts. There was a significant difference between the hosts in the number of days taken to reach the first moult by the ‘stricta’ biotype of D. opuntiae. There was evidence that the ‘stricta’ biotype of D. opuntiae exhibited varying degrees of acceptability on the Opuntia hosts. The most acceptable and suitable hosts for the ‘stricta’ biotype of D. opuntiae were O. stricta and O. humifusa. Secondly, I investigated some factors that might determine whether the ‘stricta’ biotype of D. opuntiae accepts or rejects a certain Opuntia as its host. The morphological and phytochemical aspects of the Opuntias were studied. Light microscopy revealed no significant differences in the thickness of the cuticle, epidermis and hypodermis of the Opuntia hosts but revealed many red particles, presumed to be tannins in the O. engelmannii lineages. The tannins, titratable acidity and pH of the Opuntia hosts’ cladodes were studied. To determine the titratable acidity, cladode samples were collected every 3 hours from 0800hrs and for pH determination cladodes were harvested between 1300hrs and 1400hrs. Estimation of the tannins was done by the Folin-Denis’ Method. The tannins and pH were significantly different between the Opuntias. Tannins ranged between 3.1-8.4 mg Tannic acid/g and were in the following rank order: O. engelmannii-Limpopo lineage > O. engelmannii-Kenya lineage > O. humifusa > O. stricta. IV The pH ranged between 5.1-7.4 and cladodes from the most acceptable hosts of the ‘stricta’ biotype of D. opuntiae had organic acids that were acidic compared to the slightly alkaline ones on the least acceptable hosts - O. engelmannii lineages. These results suggest that tannins and pH of the Opuntias may be the basis of host selection in this cochineal insect. The impact of the ‘stricta’ biotype of D. opuntiae’s herbivory on the physiology of the acceptable and suitable hosts were examined by monitoring chlorophyll concentration changes and the diurnal changes in photochemical efficiency of the Opuntias. The chlorophyll concentration and the photochemical efficiency of PS II decreased as D. opuntiae herbivory increased. These physiological results show that the ‘stricta’ biotype of D. opuntiae could result in the successful biological control of O. humifusa in South Africa
Presented to the Faculty of Science at the University of the Witwatersrand in Fulfilment of the Requirements For a degree of Doctor of Philosophy School of Animal, Plant and Environmental Sciences Johannesburg May 2018
Keywords: Cactus; House plants